Fatores associados aos níveis séricos de IgE Total em residentes de uma área endêmica para esquistossomose de Minas Gerais - Leonardo Ferreira Matoso (2008)
This study aimed to evaluate the relationship between socioeconomic, demographic, water contact, reinfection with S. mansoni and the levels of IgE total in patients from 340 residents of the endemic area of Ponto dos Volantes, Minas Gerais. Demographic, socioeconomic and water contact behavior data were collected using a questionnaire developed by our group. Three stool samples were collected using the Kato-Katz method. Total IgE levels were evaluated in ELISA using sera collected from enrolled individuals. The prevalence for S. mansoni before treatment was 65% (CI95% 58.72-71.28) with the geometric mean egg count 59.27(CI95% 54.93-63.61). After one year of the treatment the prevalence was reduced to 13.8% (CI95% 6.01-21,50) and the geometric mean egg count was to 24.33 (CI95% 17.70-30.96) this difference was statistically significant. Before treatment the higher rates of infection intensity were observed in patients in the age group of 15-29 and higher prevalence in the age group of 30-49. After treatment, the higher intensity, prevalence and reinfection were higher in the age group of 6-14 when compared to other age groups. The IgE total (mg/mL) level before treatment was 7.8 (CI95% 6.6-9.6) and after treatment was 3.8 (CI95% 3.2-4.3) with p>0.01. Total IgE (mg/mL) levels increased with the age and were higher in male individuals. The lowest median total IgE levels were observed among schistosomiais negative individuals then reinfected and not reinfected individuals, this difference was statistically significant. Linear Regression Model was used to examine the data both on individual and household levels and to evaluate the correlation between all independent variables and total levels IgE (mg/mL) after treatment. The multivariate analysis showed that crossing stream was related to age, sex, having shower, total TBM and schistosomiasis were correlated and statistically significant with total levels IgE after treatment. Theses results showed that these variables have an important effect on total IgE levels after treatment and that higher total IgE levels after treatment seems to be a predictive factor of reinfection by S. mansoni.